Cross-border cooperation between Ukraine and Poland - Turka, Nataliya (Wydawnictwo Uniwersytetu Wrocławskiego, 2013)
The article introduces the characteristics of cross-border cooperation of western regions of Ukraine and Poland. The Cross-border Cooperation Programme “Poland-Belarus-Ukraine 2007– 2013” was analysed and the economic aspects of the Euroregions “Bug” and “Carpathian” were examined.
Keywords: cross-border cooperation; Euroregion; Ukraine; Poland; EU